2015
DOI: 10.1007/s12035-015-9568-5
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 14 Modulates the Neurogenesis of Granule Neurons in the Adult Dentate Gyrus

Abstract: Adult neurogenesis, the production of mature neurons from progenitor cells in the adult mammalian brain, is linked to the etiology of neurodegenerative and psychiatric disorders. However, a thorough understanding of the molecular elements at the base of adult neurogenesis remains elusive. Here, we provide evidence for a previously undescribed function of fibroblast growth factor 14 (FGF14), a brain disease-associated factor that controls neuronal excitability and synaptic plasticity, in regulating adult neurog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 85 publications
(104 reference statements)
3
25
1
Order By: Relevance
“…Compelling evidence indicates that FGF14 is a relevant accessory protein of the Nav channel complex (Hsu et al, 2015; Ali et al, 2016; Alshammari et al, 2016a; Tempia et al, 2015; Shavkunov et al, 2013; Bosch et al, 2015), responsible for action potential initiation and propagation in neurons. In previous studies, we showed that FGF14 forms a complex with neuronal Nav1.6 channel, and this interaction is controlled by S/T kinases (Hsu et al, 2015, 2016; Shavkunov et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Compelling evidence indicates that FGF14 is a relevant accessory protein of the Nav channel complex (Hsu et al, 2015; Ali et al, 2016; Alshammari et al, 2016a; Tempia et al, 2015; Shavkunov et al, 2013; Bosch et al, 2015), responsible for action potential initiation and propagation in neurons. In previous studies, we showed that FGF14 forms a complex with neuronal Nav1.6 channel, and this interaction is controlled by S/T kinases (Hsu et al, 2015, 2016; Shavkunov et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…In mice, targeted disruption of FGF14 produces severe ataxia, paroxysmal dystonia, and cognitive impairment (Wang et al, 2002; Wozniak et al, 2007), with neurons that exhibit severe impairments in synaptic transmission and plasticity, and neuronal excitability (Alshammari et al, 2016a,b; Xiao et al, 2007; Wozniak et al, 2007). Significantly, the assembly and trafficking of FGF14 itself is controlled via a GSK–3 dependent signaling pathway that may critically regulate excitability through PPI at the level of the Nav complex (Hsu et al, 2015; Shavkunov et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…During both critical periods, numerous factors increase new neuron numbers, 'rescuing' new neurons that would otherwise have died [Shors, 2008;Anderson et al, 2011;Curlik and Shors, 2011;Waddell et al, 2011]. At a mechanistic level, factors that rescue new neurons include neurotrophins such as BDNF [Alvarez-Borda et al, 2004], testosterone and its metabolites [Rasika et al, 1999;Yamamura et al, 2011;Alward et al, 2016] and other growth factors [Alshammari et al, 2015;Joppe et al, 2015;Bakos et al, 2016]. At a behavioral level, neuronal lifespan is influenced by exercise [van Praag et al, 1999;van Praag, 2008], stress [Gould et al, 1997], sleep [Guzman-Marin et al, 2005], social conditions [Lipkind et al, 2002;Alward et al, 2014;Holmes, 2016], learning [Shors et al, 2001[Shors et al, , 2002, and use of the brain region in the absence of learning [Li et al, 2000;Pytte et al, 2010].…”
Section: Does Identifying Factors That Increase New Neuron Survival Imentioning
confidence: 99%